Victrix svetlanae sp. n., a new species of Bryophilinae (Lepidoptera, Noctuidae) from Far East of Russia - Koshkin, Evgeny S.; Pekarsky, Oleg (Zootaxa, 2020)
Victrix svetlanae sp. n. is described from Russian Far East, Khabarovsk Krai. The new species belongs to the subgenus Poliobrya Hampson, 1908. New species is most similar to V. umovii (Eversmann, 1846) and V. patula (Püngeler, 1907) but differs in both external and genital characteristics. This is the first record of the genus Victrix in the Far East.